Gambaran Tingkat Pengetahuan Ibu Balita tentang Stunting di Posyandu Camelia Kecamatan Rawalumbu Kota Bekasi: Overview of Mothers’ Knowledge Level about Stunting at Camelia Posyandu, Rawalumbu District, Bekasi City - Ananda Prastuti Sutrisno; Ratna Komala; Rahmi Fitri Kentiasti; Shanti Hekmawati (Journal of Nursing Education and Practice, 2025)
Introduction: Stunting is a chronic nutritional problem that impairs children's physical and cognitive development. A mother's knowledge is a crucial factor in preventing stunting, as it influences her behavior and decisions regarding child nutrition and care. Objectives: This study aimed to describe the level of knowledge about stunting among mothers of toddlers at the Posyandu Camelia, Rawalumbu District, Bekasi City. Method: This quantitative descriptive study used a cross-sectional approach. A sample of 27 mothers was selected using consecutive sampling during February 2025. Data were collected using a questionnaire and analyzed using univariate analysis. Knowledge was categorized as good (76-100%), sufficient (56-75%), and poor (<56%). Result: The majority of respondents were aged 20–30 years (55.56%), had a bachelor's degree (59.26%), and were unemployed (70.37%). The study found that most mothers (55.56%) had a poor level of knowledge about stunting, while 25.93% had a sufficient level, and only 18.52% had a good level. Conclution: A significant portion of mothers at Posyandu Camelia have a poor level of knowledge regarding stunting, despite a high level of formal education. This highlights a gap between formal education and practical health literacy, emphasizing the need for more intensive and targeted health promotion programs. Keywords: knowledge, mother, stunting